Elucidating the crystal structure of the antimalarial drug (+/-)-mefloquine hydrochloride: a tetragonal hydrated species - Prado, Vania Mendes do; Seiceira, Rafael Cardoso; Pitaluga, Altivo; Andrade-Filho, Tarciso; Alves, Wendel Andrade; Rocha, Alexandre Reily [UNESP]; Ferreira, Fabio Furlan (Wiley-Blackwell, 2014)
Albeit widely studied, the structure of the antimalarial drug (+/-)-mefloquine hydrochloride is still a controversial issue. A combination of X-ray powder diffraction, theoretical calculations and Fourier transform-infrared spectroscopy is used to unambiguously determine the crystal structure of the molecule in its active pharmaceutical ingredient. It is demonstrated that water is incorporated into the structure, leading to a hydrated form and, most importantly, to significant differences in both structure and bonding. Such changes can lead to significant differences in biological activity. (C) 2014 International Union of Crystallography